Managing students’ anxiety while learning foreign languages in the conditions of war in Ukraine - Shyba, Alona (Young Scientist, 2023)
The current tense situation in which Ukraine found itself due to Russia’s military aggression in fluenced all spheres of life: social, economic, medical, environmental and educational. And if traditionally the main factors determining the efficacy of foreign languages teaching and learning were methods and techniques used by the teacher, students’ mental capacities and cognitive knowledge of the target language and moti vation, in today’s situation when a classroom ceased being a safe place, the priorities have shifted. Affective factor became essential, as depending on whether positive or negative emotions prevail, our mental processes while learning can be either boosted or hampered. In the process of foreign language teaching and learning the following affective factors should be taken into account: students’ self-esteem, risk-taking, motivation, anxiety and inhibition. Due to the current situation in Ukraine, learners’ anxiety became the object of our research. Ukrainian students, those learning foreign languages in particular, are facing now the difficulties connected with a high anxiety level. The research conducted at the faculty of foreign languages of Yuriy Fedkovych Cher nivtsi National University proved an extremely high level of students’ situational anxiety, which is not only hampering their ability to learn, but has a drastic effect on students’ health. The teachers have to face the challenge of lowering their learners’ anxiety, conducting the academic process in the condition of war.
Keywords: foreign language teaching, foreign language learning, affective factors, anxiety, war anxiety, learning anxiety.